2011
DOI: 10.1002/sia.3857
|View full text |Cite
|
Sign up to set email alerts
|

Surface science aspects of supramolecular conformation in elastin‐like polypeptides

Abstract: Polypeptides can form helical fibres in aqueous media: potentially useful for the production of biocompatible fabric and yarns. A previous work has shown that fibre formation occurs readily with elastin-like polypeptides constructed from hydrophobic amino acids, such as valine, glycine and leucine. However, elastin-like polypeptides, when suspended in methyl alcohol, are observed to form globules and 'string of bead' structures. Thus, it seems probable that the interface energy is important. Interface energy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 42 publications
3
10
0
Order By: Relevance
“…In Figure 1, results from surface analyses of poly(ValGlyGlyValGly) suspended in 50% MeOH, that is, MeOH/H 2 O 1:1 mixture deposited on gold are summarized. These experiments with poly(ValGlyGlyValGly) in methanol/water mixtures retrace those previously performed with poly(ValGlyGlyLeuGly) in MeOH, MeOH:H 2 O 1:1, MeOH:H 2 O 1:213 and further support the evidence of AFM and XPS, that these polypeptides have similar solvation paths: the proportions of different, coexisting, structures correlate with the relative water/methanol activities and the relative evaporation rate of the two solvents (vapor pressure of 13.02 kPa for methanol and 2.3 kPa for water, at 20°C).…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…In Figure 1, results from surface analyses of poly(ValGlyGlyValGly) suspended in 50% MeOH, that is, MeOH/H 2 O 1:1 mixture deposited on gold are summarized. These experiments with poly(ValGlyGlyValGly) in methanol/water mixtures retrace those previously performed with poly(ValGlyGlyLeuGly) in MeOH, MeOH:H 2 O 1:1, MeOH:H 2 O 1:213 and further support the evidence of AFM and XPS, that these polypeptides have similar solvation paths: the proportions of different, coexisting, structures correlate with the relative water/methanol activities and the relative evaporation rate of the two solvents (vapor pressure of 13.02 kPa for methanol and 2.3 kPa for water, at 20°C).…”
Section: Resultssupporting
confidence: 77%
“…In accord with findings of previous work9–13 and literature,14–17 we show that water molecules have a unique role in organizing the fibrillar structure. Supported by computation, these studies have allowed the revaluation of the 3D model previously proposed11 for the self‐assembly of poly(ValGlyGlyValGly), the polypeptide most inclined to form helical fibers in water.…”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…A discussion of the possible impact of surface chemistry on amyloid-like fibre conformation has been given. [4] More recently, a multi-technique study of the trimer, (ValGlyGlyValGly) 3 , has been carried out. [4,5] This contribution, part of the multi-technique study, deals specifically with the helical formations that were found when samples of the trimer in aqueous suspension were examined within a few hours of its preparation.…”
Section: Introductionmentioning
confidence: 99%